2022
DOI: 10.3389/fneur.2022.813597
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Repetitive Transcranial Magnetic Stimulation for Post-stroke Vascular Cognitive Impairment: A Prospective Pilot Study

Abstract: ObjectivePost-stroke cognitive impairment (PSCI) is resistant to treatment. Recent studies have widely applied repetitive transcranial magnetic stimulation (rTMS) to treat various brain dysfunctions, such as post-stroke syndromes. Nonetheless, a protocol for PSCI has not been established. Therefore, this study is aimed to evaluate the therapeutic effect of our high-frequency rTMS protocol for PSCI during the chronic phase of stroke.MethodsIn this prospective study, ten patients with PSCI were enrolled and rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Evidence from the animal study suggests that the neuroprotective and pro-cognitive effects of TMS may exert by enhancing neurogenesis and activating BDNF/TrkB signaling pathway. A prospective pilot study conducted recently demonstrate that the scores of several cognitive evaluations increased after completion of the TMS session (34), which is similar to the results of pooled data in our study. However, it is worth noting that the stimulus parameters for TMS of the studies included in our network meta-analysis were not entirely consistent and subgroup analyses were not performed due to the limited literature, which may affect the reliability of the results to some extent.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence from the animal study suggests that the neuroprotective and pro-cognitive effects of TMS may exert by enhancing neurogenesis and activating BDNF/TrkB signaling pathway. A prospective pilot study conducted recently demonstrate that the scores of several cognitive evaluations increased after completion of the TMS session (34), which is similar to the results of pooled data in our study. However, it is worth noting that the stimulus parameters for TMS of the studies included in our network meta-analysis were not entirely consistent and subgroup analyses were not performed due to the limited literature, which may affect the reliability of the results to some extent.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the rehabilitation and stimulation groups showed significantly lower levels of IL-17A and TNF-α, which tended to be at normal range, and higher levels of VEGF-A, which deviated even more from normal after intervention. These results suggest that both conventional rehabilitation and MDSS therapy were effective in inhibiting the secretion of pro-inflammatory cytokines (i.e., IL-17A and TNF-α) and promoting the production of nerve regeneration factor VEGF-A, thereby reducing neurological impairment and accelerating cognitive and limb motor function recovery (Zhang et al, 2021;Cha et al, 2022). There was no significant difference in the IL-17A, TNF-α, and VEGF-A levels, or the NIHSS, MMSE, FMA, and MBI results between the rehabilitation and stimulation groups after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a 2-week course of low-frequency rTMS (1 Hz) was effective in patients with Parkinson’s disease and UD, suggesting that rTMS could be effective in other neurological disorders with UD ( Brusa et al, 2009 ). A prospective study of 10 patients with post-stroke cognitive impairment receiving 2 consecutive weeks (5 days per week) of high-frequency rTMS (20 Hz) to the ipsilateral dorsolateral prefrontal cortex showed that treatment improved cognitive function and changed brain networks associated with post-stroke cognitive impairment, which lasted at least 3 months ( Cha et al, 2022 ). Although rTMS is now widely used for stroke survivors ( Kim et al, 2020 ; Lefaucheur et al, 2020 ), there are no clinical studies related to rTMS in patients with UD, and VCI and further studies are required.…”
Section: Treatmentsmentioning
confidence: 99%